The convergence of environmental crime with other serious crimes: Subtypes within the environmental crime continuum - van Uhm, Daan P. (European journal of criminology, 2022)
The rising global scarcity of natural resources increasingly attracts transnational criminal organizations. Organized crime syndicates diversify into the lucrative business of tropical timber, endangered species, and natural minerals, alongside their traditional activities. The developing interconnectedness between environmental crime and other serious crimes shows that traditional lines of separation are no longer appropriate for understanding and dealing with the increasing complexities of organized crime. Therefore, this article aims to analyse the nexus between environmental crime and other serious crimes through cluster analyses to identify subtypes of organized crime groups that have diversified into the illegal trade in natural resources. The two-step cluster algorithm found a cluster solution with three distinct clusters of subtypes of criminal groups that diversified into the illegal trade in natural resources in various ways: first, the Green Organized Crime cluster, with a high degree of diversification and domination; second, the Green Opportunistic Crime cluster, with flexible and fluid groups that partially diversify their criminal activities; and, third, the low-level diversifiers of the Green Camouflaged Crime cluster, shadowing their illegal businesses with legitimate companies. The three clusters can be related to specific stages within the environmental crime continuum, albeit with nuances.